Addressing the regulatory impediments constraining Tanzania firms from leveraging market access opportunity under African growth opportunity act - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
The African Growth and Opportunity Act (AGOA) is a trade arrangement scheme between the United States of America and eligible sub-Saharan African (SSA) countries. It offers nonreciprocal preferential treatment over 7000 products exported from African countries to the US market. AGOA is one among a number of trade preferential schemes that Tanzania is eligible. The Act provides for issues such as but not limited to trade and investment. Tanzania has a history of poor export performance despite the preferential treatment. This legal study examines the existing legal and regulatory framework governing trade and investment in an attempt to identify regulatory weaknesses resulting in Tanzania's poor trade performance. Also, the study indulges in Kenya's experience under AGOA to find whether Tanzania may draw lessons from the country success story under the preferential arrangement. The study then formulates recommendations in view of improving Tanzania's trade enabling framework to increase exports and potentially become a regional trade hub including establishing an effective national AGOA strategy.